ANALISA YURIDIS AKIBAT HUKUM PERCERAIAN GHOIB DALAM PANDANGAN HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN (Studi Pada Putusan Nomor: 130/Pdt.G/2013 /PA.MTR) - Rifqi Munadi; Fatahullah Fatahullah (Private Law, 2021)
Purposes of this work are to know and to analyse legal consequences of “ghaib” divorce (a divorce which conducted against uncontacable husband/wife) in the view of Islamic law and law on marriage in the Verdict Number 130/Pdt.G/2013/PA.MTR. applied method of this work is normative legal research. Judge’s consideration in the Verdict Number 130/Pdt.G/2013/PA.MTR based on laws and facts has been fulfill the divorce requirements as regulated in the Explanation of Article 19 letter (f) Government Regulation Number 9 of 1975 and Article 116 letter f Islamic Compilation Law. Therefore, in this judge’s verdict it imposing First Talaq Ba’in Shugraa of the applicant to defendant. Legal consequences of uncontactable husband divorce according to Islamic Compilation Law it can be articulate as first talaq ba’in shugraa. However, in the Marriage Law this term is unknown, thus its legal consequences had the same effect as regular divorce.